Economy of Fertilizer Nitrogen through Organic Sources in Rain-Fed Rice-Legume Cropping Systems in West Bengal, India - A.M. Puste; S. Bandyopadhyay; D.K. Das (The Scientific World Journal)
Field experiments were conducted at a farmers’ plot adjacent to the Regional Research Station, red and laterite zone, Sub-center Sekhampur (Birbhum district) of West Bengal, India, situated 23° 24' N latitude, 87° 24' E longitude, to study the effect of different bio- and organic sources of nutrients instead of total fertilizer N in terms of crop productivity in the sequence and building up of soil fertility. During the wet seasons of 1997 and 1998, 12 combinations of bio- and organic sources (crop residues, well decomposed cow dung, dhanicha as green manure) were substituted for 25–50% of N fertilizer applied on transplanted rice (Cv. IR 36). Subsequently, during the winters of 1997–1998 and 1998–1999, leguminous pulse crops like lentil (Lens culinaris [L.] Medic.), gram (Cicer arietinum L.) and lathyrus (Lathyrus sativus L.) were grown with and without inoculation of Rhizobium. Results revealed that the application of inorganic N in combination with organic sources exhibited a significant increase in rice yield (3.60–3.84 t ha-1) compared to the yield from sole application of N (3.19–3.26 t ha-1). The study showed that about 25% of total applied N was saved without significant yield reduction with simultaneous improvement of soil physical properties (pH, organic matter, available N, P, K, and CEC). Seed yield of pulses (lentil, gram, and lathyrus) were more pronounced in the treatment inoculated with Rhizobium, with a saving of 42.6–48.4 kg N ha-1. Therefore, the results suggest that the combined application of inorganic and organic N sources in a 75:25 ratio is a superior N-management practice with regards to crop yields as well as improvement of soil fertility.